The Interior Design of Domestic Departure Hall of Tanjung Emas Port Semarang with Venetie Van Java Concept - Jaza Chehata Hadi (Institut Seni Indonesia Surakarta, 2020)
Port is a place of land surrounded by waters with certain boundaries as a place for both government and economic activities used as a place to berth, board and disembark passengers, also load and unload goods. Passenger port is a sea transportation infrastructure for the purposes of facilitating passengers sea trips in terms of their arrival and departure. Currently, PT. Pelabuhan Indonesia III is continuously improving in terms of quantity and quality. In this case, the interior design can be influential as a supporting attraction for sea transportation in Indonesia. One of them is through the design of the Tanjung Emas passenger terminal, by elevating the image of the city of Semarang through its colonial buildings which are the identity of the city of Semarang with supporting facilities based on the needs of the passengers. This design work applies the method of innovation design process by Vijay Kumar with seven modes of activities, such as: understanding objectives, knowing the context, knowing the community, compiling ideas, exploring concepts, developing solutions, and realizing offers. The design of the Tanjung Emas domestic departure terminal adopts the architectural form of Lawang Sewu and Mandiri Bank buildings in Kota Lama (old city) of Semarang and is combined with modern facilities inside.